Functional evolution of cis-regulatory modules of STMADS11 superclade MADS-box genes - Khan, Muhammad Ramzan; Ali, Ghulam Muhammad (Plant molecular biology, 2013)
Evolution of phenotypic morphologies is closely associated with modular organization of cis -regulatory elements underlying expression divergence. The MADS-box gene family is the subject of extensive studies that try to unscramble the structural complexity of flowering plants. This study is envisaged to explore the potential of CRMs in highly constrained non-coding elements of STMADS11 superclade MADS-box genes in expression divergence. Phylogenetic reconstruction differentiated the STMADS11 genes into SVP - like , ZMM19 - like, MPF1 - like and MPF2 - like clades. Differential gene expression in vegetative and floral organs was evident within the clades as well as at inter-clade level. The genomic DNA search for clusters of short motifs and sequence conservation of the −2 kb promoter region of particularly, MPF2 - like clade permitted to establish three well defined CRMs where transcription factors bind, being CRM1 the activator, CRM2 the repressor, and CRM3 the enhancer element. Similar clusters were also mapped in the large 1st introns in the coding region. Within these CRMs many transcription factor-binding sites, particularly the hotspots for MADS-domain TF binding elements—CArG-boxes, directing sepal specific expression in Arabidopsis —were accrued in the CRM1 of MPF2 - like promoters. Site-directed mutagenesis and motif swapping through reporter assays allude towards their implication as functionally active elements. In terms of directional evolution of MPF2 - like promoters, CRMs are significantly more conserved than flanking regions, hence, bearing the signatures for purifying selection. Thus, CRMs are the pervasive feature of STMADS11 genes and mutations and/or appearance of new transcription factor binding sites and position of the CRMs are responsible for the divergence in expression patterns in this clade. These results have implications in understanding functional evolution of cis -regulatory modules in plants.